Implementation of Design Thinking on Match-up Interactive Media for Cell Learning - Zulkfiri S.Pou; Siti Rahmatia Badari; Martavina Yustita Pala; Dsiya Auralia Askanita; Moh. Dhuhri Surya Wirawan; Rita Lefrida (Postgraduate, University of Mataram, 2024)
Student-centered learning is able to bring out the creative and innovative thinking of students which are needed to face the twenty-first century's challenges. A mindset that can bring out the creative potential in everyone is Design Thinking. The current study employed a theoretical perspective from design thinking with problem-solving activities consisting of 5 stages, namely emphatize, define, ideate, prototype, and test. In-depth observations and interviews were conducted to identify problems faced by high school students at SMA Negeri 6 Palu. Sample selection was based on criteria of extreme right sample and extreme left sample. The results obtained in the form of Interactive media in the form of Match-ups as discussion material and gamification on cell material were designed to be used in the learning process.